International Monetary Fund Annual Report 1957. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1957)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1957. The report highlights that boom conditions continued throughout 1956, sustained by an undercurrent of private business investment sufficiently strong to compensate for such weaknesses as appeared in some individual sectors. Any apprehensions, which might have been entertained in the early months of the year that the upward trend of business was soon to be reversed, were thus shown to be without foundation.